Implementation analysis of a case management intervention for people with complex care needs in primary care: a multiple case study across Canada - Catherine Hudon; Mathieu Bisson; Maud-Christine Chouinard; Alannah Delahunty-Pike; Mireille Lambert; Dana Howse; Charlotte Schwarz; Olivier Dumont-Samson; Kris Aubrey-Bassler; Fred Burge; Shelley Doucet; Vivian R. Ramsden; et al. (BMC, 2023)
Abstract Background Case management is one of the most frequently performed interventions to mitigate the negative effects of high healthcare use on patients, primary care providers and the healthcare system. Reviews have addressed factors influencing case management interventions (CMI) implementation and reported common themes related to the case manager role and activities, collaboration with other primary care providers, CMI training and relationships with the patients. However, the heterogeneity of the settings in which CMI have been implemented may impair the transferability of the findings. Moreover, the underlying factors influencing the first steps of CMI implementation need to be further assessed. This study aimed to evaluate facilitators and barriers of the first implementation steps of a CMI by primary care nurses for people with complex care needs who frequently use healthcare services. Methods A qualitative multiple case study was conducted including six primary care clinics across four provinces in Canada. In-depth interviews and focus groups with nurse case managers, health services managers, and other primary care providers were conducted. Field notes also formed part of the data. A mixed thematic analysis, deductive and inductive, was carried out. Results Leadership of the primary care providers and managers facilitated the first steps of the of CMI implementation, as did the experience and skills of the nurse case managers and capacity development within the teams. The time required to establish CMI was a barrier at the beginning of the CMI implementation. Most nurse case managers expressed apprehension about developing an "individualized services plan" with multiple health professionals and the patient. Clinic team meetings and a nurse case managers community of practice created opportunities to address primary care providers' concerns. Participants generally perceived the CMI as a comprehensive, adaptable, and organized approach to care, providing more resources and support for patients and better coordination in primary care. Conclusion Results of this study will be useful for decision makers, care providers, patients and researchers who are considering the implementation of CMI in primary care. Providing knowledge about first steps of CMI implementation will also help inform policies and best practices.